EVALUATION OF ACUTE AND SUBACUTE ORAL TOXICITY INDUCED BY HYDROALCOHOLIC EXTRACT OF IPOMOEA ERIOCARPA IN EXPERIMENTAL RATS - KOMAL MANWANI; MOHD. SAIFUL ISLAM; MAYUR PORWAL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: The study aimed to investigate the acute and subacute oral toxicity caused by the hydroalcoholic extract of Ipomoea eriocarpa in albino Wistar rats. Methods: The acute toxicity assessment involved administering a limit dose of 2000 mg/kg body weight, followed by daily assessments for an additional 14 days. The rats were weighed and assessed for mortality, behaviour, and signs of illness. In the subacute study, four groups of ten rats were administered distilled water and the extract at doses of 200, 1000, and 1800 mg/kg every 24 hours for 28 days. Results: The animals' organ weight, haematological analysis, and biochemical parameters were evaluated and showed no significant difference when compared to the control group. The histopathological examination of the vital organs of the animals was conducted to assess gross findings in comparison to the control group. No significant difference (p > 0.05) was observed in the relative organs, body weights, haematological and biochemical parameters, as well as gross abnormalities when compared to the control group. No instances of mortality were documented. Investigations into toxicity are essential for guaranteeing the safety of chemicals, pharmaceuticals, and other materials. They safeguard human health and the environment, facilitate regulatory decision-making, inform product development, and enhance scientific comprehension of negative impacts. Conclusion: The study concluded that the short-term and medium-term oral administration of the hydroalcoholic extract I. eriocarpa to rats did not induce toxicity. The oral administration of the extract to rats demonstrated a significant margin of safety and holds promise for the development of a novel medicinal agent.